The landscape of actionable genomic alterations in lung adenocarcinomas in India - Sharma, Rakesh; Kamireddy, Aruna Priya; Hussaini, Syed Meera; Chatterjee, Soma; Hasan, Qurratulain; Jain, Jugnu (Frontiers in Genetics, 2023)
Lung adenocarcinoma (LUAD), the most prevalent form of non-small cell lung cancer (NSCLC), remains a leading cause of cancer-related death globally, including in India, with a 5-year survival rate below 10%. Despite these grim statistics, recent advances in the use of next-generation sequencing (NGS) for identifying genetic alterations and the emergence of targeted therapies have opened new possibilities for personalized treatment based on distinct molecular signatures. To understand the molecular pattern of NSCLC, a retrospective study was conducted with 53 Indian LUAD patient samples, using a targeted NGS panel of 46 cancer-relevant oncogenes to identify clinically relevant variants. Pathogenic or likely pathogenic variants were detected in 94% of the 53 cases. Non-synonymous mutations, rearrangements, copy number alterations, insertions, and deletions of functional relevance were observed in 31 out of 46 genes. The most frequently mutated genes included TP53 (52.8%) and EGFR (50.9%), followed by RET, PIK3CA and ERBB2; some patients had multiple alterations in the same gene. Gender-based enrichment analysis indicated that ALK and IDH2 alterations were more prevalent in females, while TP53 and PTEN were more common in males. No significant correlation was found between mutations and other clinicopathological attributes, such as age, stage, and subtype. A higher prevalence of EGFR, RET, PIK3CA, ERBB2 and ALK mutations were observed compared to previous LUAD genetic studies coupled with a lower frequency of KRAS mutations. Clinically actionable variants were annotated using OncoKB and categorized into the four therapeutic levels based on their clinical evidence. Seventy-nine percent of cases had at least one clinically actionable alteration. Most patients (39.6%) had the highest level of actionability (Level 1) wherein an FDA-approved drug is available specifically for the observed mutation in lung cancer patients. EGFR Exon19 in-frame deletions and EGFR L858R were the most frequent among targetable variants (20.7%). These findings emphasize the importance of a selective NGS panel in enabling personalized medicine approaches by identifying actionable molecular alterations and informing the choice of targeted therapy for more effective treatment options in Indian NSCLC patients.